Implementation of Restorative Justice as an Alternative to Overcome Prison Overcapacity at Bagan Siapi-api Prison - Mulkanuddin; Risdalina; Kusno (Faculty of Law, University of Dr. Soetomo, 2026)
Prison overcapacity has become a structural issue within Indonesian correctional institutions, including Bagan Siapi-api prison. The excessive number of inmates affects institutional effectiveness, rehabilitation programs, and the protection of prisoners’ rights. This study examines how restorative justice may function as an alternative legal mechanism to mitigate prison overcapacity in Bagan Siapi-api Prison. Employing normative and empirical juridical approaches, this research analyses both regulatory frameworks and their practical implementation. The findings demonstrate that restorative justice, particularly in cases involving minor offenses, contributes to reducing the influx of inmates into correctional facilities. Nevertheless, its application is not yet optimal due to regulatory constraints, limited institutional capacity, and the dominance of a retributive perspective among law enforcement authorities. Strengthening legal policies and institutional readiness is therefore necessary. Ultimately, restorative justice offers a sustainable approach that balances legal certainty, social restoration, and institutional efficiency.